Incidence of Neonatal microcephaly in the Hospital Cayetano Heredia, Lima, 2016 - 2017. - Samaniego Lozano, Cynthia (2019)
Objective: To determine the incidence of neonatal microcephaly in the Hospital Cayetano Heredia, throughout a well-defined period. Material and Methods: Microcephaly was determined by a cephalic perimeter lower than the third percentile for age and sex. Reported records of the Hospitalâ€™s Perinatal Computer System between January 1st, 2016 and December 31st, 2017, were used. Fenton growth chartâ€™s parameters were used to determine the limits of normality. Results: A total of 416 cases of neonatal microcephaly were registered, a general rate of 53.4 per 1,000 live births, up to 185 per 1000 live births in preterm infants (<37 weeks), with higher figures among males. Conclusions: A high incidence rate of microcephaly was found, probably higher in preterm infants and due to multiple causes. Observational biases cannot be discarded.